Improved performances of the wind inlet of the Savonius rotor - Dinčić, Dejan D.; Despotović, Milan Z. (Vojnotehnički glasnik / Military Technical Courier, 2016)
In this study we analyzed the design changes through increasing vertical angles of the top and bottom plates of the wind inlet of a Savonius rotor, in order to obtain better results and better system performances. A designed wind inlet is placed in the front part of the rotor in order to prevent negative torque opposing rotor rotation. The geometric parameters of the wind inlet are determined to obtain optimal performances. Analyses and tests have shown that the increase of the vertical angles of the top and bottom plates on the wind inlet of a Savonius rotor leads to better rotor performances in comparison to the use of a classic wind inlet. It was found that the best results are achieved with increasing vertical angles of the top and bottom plates of the Savonius rotor wind inlet for a total of 15°, where the rotor speed is 395 revolutions per minute.
Keywords: vertical angles; wind; Savonius rotor; Rotors; plates; Editorials